El Nuevo Modelo de Gestión Educativa y su incidencia en el desarrollo de la educación intercultural bilingüe de la provincia de Cotopaxi. Estudio de caso en la escuela Remigio Crespo Toral de la comunidad de Cachi Alto - Ramón Arias, Mariana de Jesús (2015)
This research bases its study on the changes proposed by the Ministry of Education, through the implementation of the New Model of Educational Management which has divided the system in: intercultural and bilingual intercultural, causing a negative and detrimental impact on students of bilingual schools in the rural sector. The implementation of the new model of educational management among others, proposes the treatment of contents with cultural and bilingual occasion suitable for the bilingual system, however it is evident that it has not guaranteed the strengthening of culture and language, causing the loss of relevance and of being indigenous. The problem risen in bilingual educational institutions, point out responsibilities in the organization and management of resources for this sector, who are immersed in bilingual institutions require intercultural training which allows the application of strategies that strengthen its management over the medium and long term. For the consolidation of culture, it is necessary to count with professionals with proactive attitude, authorities who get involved with educational work in the same context, willing to change, with leadership skills to reinforce the linguistic-cultural and academic values in students of "Remigio Crespo Toral" elementary bilingual school. In Chapter I the problem is posed, the causes and the consequences are enounced, the objectives of the research are formulated, the justification and importance of the education and culture strengthening. Chapter II is about the theoretical framework that founds important aspects like structures, processes, basic theories, identity principles and intercultural. Chapter III is centered on the research and collecting data procedures; in addition, the processing and discussion of the results obtained. Chapter IV talks about the proposal